Human blood dendritic cell antigen 3 (BDCA3)+ dendritic cells are a potent producer of interferon‐λ in response to hepatitis C virus12. Issue 5 (14th March 2013) - Yoshio, Sachiyo; Kanto, Tatsuya; Kuroda, Shoko; Matsubara, Tokuhiro; Higashitani, Koyo; Kakita, Naruyasu; Ishida, Hisashi; Hiramatsu, Naoki; Nagano, Hiroaki; Sugiyama, Masaya; Murata, Kazumoto; Fukuhara, Takasuke; et al.
Abstract: The polymorphisms in the interleukin ( IL)‐28B (interferon‐lambda [IFN]‐λ3) gene are strongly associated with the efficacy of hepatitis C virus (HCV) clearance. Dendritic cells (DCs) sense HCV and produce IFNs, thereby playing some cooperative roles with HCV‐infected hepatocytes in the induction of interferon‐stimulated genes (ISGs). Blood dendritic cell antigen 3 (BDCA3) + DCs were discovered as a producer of IFN‐λ upon Toll‐like receptor 3 (TLR3) stimulation. We thus aimed to clarify the roles of BDCA3 + DCs in anti‐HCV innate immunity. Seventy healthy subjects and 20 patients with liver tumors were enrolled. BDCA3 + DCs, in comparison with plasmacytoid DCs and myeloid DCs, were stimulated with TLR agonists, cell‐cultured HCV (HCVcc), or Huh7.5.1 cells transfected with HCV/JFH‐1. BDCA3 + DCs were treated with anti‐CD81 antibody, inhibitors of endosome acidification, TIR‐domain‐containing adapter‐inducing interferon‐β (TRIF)‐specific inhibitor, or ultraviolet‐irradiated HCVcc. The amounts of IL‐29/IFN‐λ1, IL‐28A/IFN‐λ2, and IL‐28B were quantified by subtype‐specific enzyme‐linked immunosorbent assay (ELISA). The frequency of BDCA3 + DCs in peripheral blood mononuclear cell (PBMC) was extremely low but higher in the liver. BDCA3 + DCs recovered from PBMC or the liver released large amounts of IFN‐λs, when stimulated with HCVcc or HCV‐transfected Huh7.5.1. BDCA3 + DCs were able to induce ISGs in the coexisting JFH‐1‐positive Huh7.5.1 cells. The treatments of BDCA3 + DCs with anti‐CD81 antibody, cloroquine, or bafilomycin A1 reduced HCVcc‐induced IL‐28B release, whereas BDCA3 + DCs comparably produced IL‐28B upon replication‐defective HCVcc. The TRIF‐specific inhibitor reduced IL‐28B release from HCVcc‐stimulated BDCA3 + DCs. In response to HCVcc or JFH‐1‐Huh7.5.1, BDCA3 + DCs in healthy subjects with IL‐28B major (rs8099917, TT) released more IL‐28B than those with IL‐28B minor genotype (TG). Conclusion : Human BDCA3 + DCs, having a tendency to accumulate in the liver, recognize HCV in a CD81‐, endosome‐, and TRIF‐dependent manner and produce substantial amounts of IL‐28B/IFN‐λ3, the ability of which is superior in subjects with IL‐28B major genotype. (HEPATOLOGY 2013)